2020
DOI: 10.1097/pai.0000000000000688
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry in the Detection of Early Myocardial Infarction: Systematic Review and Analysis of Limitations Because of Autolysis and Putrefaction

Abstract: The postmortem diagnosis of acute myocardial infarction is one of the main problems in forensic practice, especially in cases in which death occurs soon after (from minutes to a few hours) the onset of the ischemic damage. Several authors have highlighted the possibility to overcome the limits of conventional histology in this diagnosis by utilizing immunohistochemistry. In the present research, we examined over 30 scientific studies and picked out over 20 main immunohistochemical antigens analyzed with a view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 50 publications
0
13
0
18
Order By: Relevance
“…Most of the studies carried out by immunohistochemical analysis of the C5b-9 marker have demonstrated the simplicity and reproducibility of the method itself. Moreover, C5b-9 represents the only marker tested for post mortem stability showing positive results that support the value in advanced autolysis or putrefaction [22,23,71]. Thus, the analysis of C5b-9 in forensic cases of suspected myocardial ischemia can be recommended.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Most of the studies carried out by immunohistochemical analysis of the C5b-9 marker have demonstrated the simplicity and reproducibility of the method itself. Moreover, C5b-9 represents the only marker tested for post mortem stability showing positive results that support the value in advanced autolysis or putrefaction [22,23,71]. Thus, the analysis of C5b-9 in forensic cases of suspected myocardial ischemia can be recommended.…”
Section: Discussionmentioning
confidence: 89%
“…EMI diagnosis can be problematic for forensic pathologist because the gross analysis and the routine hematoxylin and eosin (H&E) staining of the heart provide no specific signs [22]; in fact, the coagulative necrosis requires several hours, thus, when death occurs after a short period (from minutes to few hours: ≤ 6-8 h) from the onset of ischemic injury, this pathognomonic sign is lacking [23]. Therefore, during the past years, several studies have been carried out to suggest investigations filling the gaps of post mortem routine analysis, highlighting the usefulness to examine the immune inflammatory and cellular factors that are involved in EMI.…”
Section: Introductionmentioning
confidence: 99%
“…Dificuldades diagnósticas da causa mortis em cadáveres decompostos. convencional (H&E), a morte deve ocorrer pelo menos de 6 a 12 horas após o início do dano isquêmico; em muitos casos, entretanto, a morte ocorre antes deste período 15 .…”
Section: Resultsunclassified
“…Em geral, após o dano isquêmico inicial, ocorre uma série de alterações estruturais das proteínas do miocárdio. A este respeito, numerosos marcadores imunohistoquímicos têm sido investigados com o propósito de identificar um IAM mais precocemente; porém continua a haver um intervalo de tempo em que os marcadores imuno-histoquímicos não podem ser avaliados e, além disso, a autólise pode alterar ou influenciar a resposta imuno-histoquímica 15 .…”
Section: Resultsunclassified
See 1 more Smart Citation